2015
DOI: 10.1099/jmmcr.0.005010
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral toxoplasmosis after rituximab therapy for splenic marginal zone lymphoma: a case report and review of the literature

Abstract: Introduction: Toxoplasma gondii is a parasite estimated to infect one-third of the global population, surviving in tissues in a latent form. Although cerebral toxoplasmosis is predominantly recognized as an opportunistic infection in hosts immunocompromised secondary to human immunodeficiency virus or bone marrow transplant, there is increasing recognition that this infection can occur in patients receiving immunomodulating agents such as mAb therapy targeted against T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Safa et al [ 6 ] reported the case of a 71-year-old woman with reactivation of cerebral toxoplasmosis following rituximab therapy, highlighting the need to consider cerebral toxoplasmosis whenever patients receiving rituximab present with neurological deficits. Similarly, Holland et al [ 7 ] described the case of a 77-year-old woman who developed cerebral toxoplasmosis while on rituximab therapy. Morjaria et al [ 8 ] reported 3 cases of reactivation of Toxoplasma encephalitis, 2 of whom were receiving rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Safa et al [ 6 ] reported the case of a 71-year-old woman with reactivation of cerebral toxoplasmosis following rituximab therapy, highlighting the need to consider cerebral toxoplasmosis whenever patients receiving rituximab present with neurological deficits. Similarly, Holland et al [ 7 ] described the case of a 77-year-old woman who developed cerebral toxoplasmosis while on rituximab therapy. Morjaria et al [ 8 ] reported 3 cases of reactivation of Toxoplasma encephalitis, 2 of whom were receiving rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the use of rituximab played a key role in the occurrence of toxoplasmosis in our patient. Indeed, opportunistic infections following completion of rituximab therapy may take place within the first months after its administration [ 6 , 7 ]. Although rituximab’s main mechanism of action is B-cell suppression, it is also hypothesized that it exerts its effects on T cells, as manifested by the occurrence of CD4+ T-cell driven opportunistic infections under rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The most clinically apparent link between lymphoma and TE relates to the administration of purine analogs, corticosteroids, and other therapies known to affect cell-mediated immunity [ 5 , 11 ]. In addition to these drugs impairing cell-mediated immunity, patients in the first 2 cases described above received rituximab, which has been posited as a risk factor for TE, although evidence is anecdotal [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reactivation of chronic toxoplasmosis was also reported following chemotherapy administration. Indeed, several cases of reactivation of cerebral toxoplasmosis following rituximab therapy were described [57][58][59][60]. The reactivation of toxoplasmosis is also a concern in solid organ transplant recipients, either as a manifestation derived from an infected donor, a reactivation of chronic toxoplasmosis in the recipient, or to a much lesser extent, a primary acquired infection following transplantation.…”
Section: Toxoplasmosis In Immunocompromised Patientsmentioning
confidence: 99%